Photo-thermal nano material capable of resisting bacteria and promoting osteogenesis through immune activation and preparation method and application of composite scaffold of photo-thermal nano material
Through the synergistic effect of XCuSi4O10 photothermal nanomaterial and Cu ions, combined with local thermal stimulation and 3D printing technology, a composite scaffold with antibacterial and bone-promoting functions was prepared, solving the problems of low antibacterial efficiency and high temperature in the prior art. The effect of effective sterilization and bone regeneration at low temperatures is achieved.
Patent Information
- Application Number
- CN202411403113.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
AI Technical Summary
Existing bone implant materials are inefficient and have too high temperature during the antibacterial process, which can damage normal tissue, affect bone regeneration, and easily lead to the development of bacterial resistance.
XCuSi4O10 photothermal nanomaterials are prepared by hydrothermal or solid phase method, combined with local thermal stimulation and Cu ions to enhance the regulation of the immune system, achieve antibacterial effects under mild conditions, and prepare a composite scaffold with porous and multilayer structure through 3D printing technology. .
Effectively kill pathogenic bacteria under low temperature conditions, while promoting bone regeneration, improving antibacterial efficiency and reducing the risk of damage to tissues, and avoiding the emergence of bacterial drug resistance.
Smart Images

Figure CN119284916A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of bone implant material preparation, and specifically relates to a photothermal nanomaterial that can activate immunity to resist bacteria and promote bone formation, and a preparation method and application of a composite scaffold thereof. Background Art
[0002] At present, surgical placement of bone implants is still the main clinical treatment option for bone trauma or defects. Affected by factors such as the surgical environment, implant sterilization conditions, and individual patient health conditions, bone infections at the injured site caused by trauma, orthopedic surgery, or joint replacement still occur from time to time. Postoperative infection not only aggravates the inflammatory response and hinders bone integration, but the proliferated bacteria can also spread to the joints / medullary cavity, causing arthritis / osteomyelitis. The main means of clinical treatment for bone infection is systemic use of antibiotics, which has the disadvantage of disrupting the balance of the body's flora and easily causing the production of drug-resistant bacteria. While fighting infection, how to promote the reconstruction and bone integration of the bone around the implant after infection treatment is another difficult problem. Therefore, the development of bone implants with both antibacterial and osteogenic activity can provide new ideas for the regeneration treatment of infected bones.
[0003] The antibacterial design of implant materials or implants for postoperative infection is mainly carried out through physical or chemical methods. The traditional design strategy includes three aspects: (1) Physical antibacterial based on microscopic morphology. The nanoprotrusions on the surface of insect wings have a strong bactericidal effect, and the bacteria on the surface die due to the mechanical rupture of the cell membrane. Based on this bionic principle, nanostructures with antibacterial functions can be manufactured, such as vertical nanoneedles, nanoknives, anti-adhesion nanostructures, etc. The vertically arranged nanoneedles on the surface can cause bacterial membrane rupture by penetrating bacteria, or cause stretching or bacterial death by generating shear force when bacteria move on the surface of nanopillars. In addition to constructing sharp nanostructures, lasers are used to manufacture nanopatterns on the surface, which can prevent bacterial adhesion by changing the hydrophilicity and roughness of the surface, thereby achieving antibacterial properties.
[0004] (2) Loading effective ingredients such as antibacterial ions or antibacterial agents on the surface of the implant. The antibacterial method of modifying the functional molecules on the surface of the antibacterial agent can kill bacteria in the tissue near the stent without direct contact between the material and the bacteria. Antibacterial agents such as metal ions, natural antibacterial agents (chitosan, antimicrobial peptides, curcumin, etc.), antibiotics, etc. are usually loaded into the stent or added to the surface coating, and are eventually released when the stent degrades. Metal ions such as Ag, Cu, and Zn can effectively inhibit the growth of Gram-positive and Gram-negative bacteria and are widely used as coatings or incorporated into orthopedic implants. The released antibacterial agents act on the bacterial cell membrane, protein, and DNA, thereby preventing the growth and reproduction of bacteria and achieving an antibacterial effect.
[0005] (3) Using implants to work in conjunction with external physical fields to achieve antibacterial effects through photothermal, photocatalytic and other technical principles. Achieving antibacterial effects through photothermal, photocatalytic and other technical principles has become a hot topic in the field of bone implant research. Photothermal antibacterial materials are mainly based on the fact that under near-infrared (NIR) light irradiation, the material absorbs light energy and converts it into heat, thereby producing an antibacterial effect through local heating. Materials with photothermal effects, such as carbon-based nanocomposites (graphene derivatives and carbon nanotubes) and metal compound nanocomposites (copper sulfide and molybdenum sulfide), can be introduced into the scaffold in the form of coatings or matrix materials. In addition, near-infrared light irradiation can enhance cell metabolism, promote angiogenesis and bone regeneration. Photocatalytic antibacterial materials refer to a method in which photocatalytic materials absorb photon energy, react with oxygen and other substances in water to generate ROS, and use ROS for antibacterial purposes. When ROS comes into contact with bacterial cell membranes, due to their strong oxidizing ability, they can destroy the bacterial cell membrane, causing the contents of the bacterial cells to flow out, ultimately leading to bacterial death.
[0006] It can be seen that the above existing technical solutions all take bacteria as the main killing target, and achieve antibacterial effect by destroying the bacterial cell membrane, inhibiting protein synthesis, disrupting bacterial metabolism, inhibiting bacterial nucleic acid synthesis and thus inhibiting its reproduction. This will inevitably lead to the problem of balancing the sterilization conditions, sterilization effects and subsequent tissue regeneration. Taking photothermal antibacterial as an example, if a better antibacterial / sterilization effect is required, the temperature needs to exceed 70°C, and this temperature has been proven to cause burns to the tissue and affect subsequent bone regeneration.
[0007] In summary, the shortcomings of the existing technology are mainly reflected in the following aspects: (1) Physical antibacterial methods can only kill adherent or directly contacted bacteria, but not bacteria floating in the blood or body fluids; (2) Chemical methods such as loading antibiotics and antibacterial ions can easily lead to bacterial resistance; (3) Thermal stimulation such as photothermal and magnetic thermal methods has a high temperature, which may burn normal tissues while killing bacteria. Therefore, how to reduce the antibacterial temperature as much as possible while maintaining excellent antibacterial efficiency and minimizing tissue damage is crucial to promoting subsequent bone regeneration. Summary of the invention
[0008] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a type of photothermal nanomaterials and composite scaffolds that can activate immunity to achieve antibacterial and promote bone regeneration, and a preparation method and application thereof, which can synergistically enhance the regulation of the immune system through thermal stimulation under mild conditions and Cu ions to achieve safe and effective antibacterial effects, so as to solve the technical defects of the prior art, such as low antibacterial efficiency, excessively high stimulation temperature that can damage normal tissues, and being unfavorable for bone regeneration.
[0009] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a photothermal nanomaterial that activates immunity to resist bacteria and promote bone formation. The molecular formula of this photothermal nanomaterial is XCuSi4O 10 , X represents Mg, Sr, Ca or Ba, etc., and the photothermal nanomaterial is a lamellar material composed of multiple crystal phases.
[0010] The present invention also discloses a method for preparing the above-mentioned photothermal nanomaterials that activate immunity to resist bacteria and promote bone growth, which can be prepared by a hydrothermal method or a solid phase method.
[0011] Among them, MgCuSi4O 10 and CaCuSi4O 10 The preparation method is hydrothermal synthesis and includes: The raw materials Mg(NO3)2·6H2O / CaCl2·2H2O, Cu(NO3)2·2.5H2O and tetraethyl orthosilicate were dissolved in water, and the pH value of the reaction system was adjusted to strong alkalinity to obtain a gel mixture; under closed conditions, the gel mixture was subjected to a hydrothermal reaction, cooled, washed and filtered to obtain MgCuSi4O 10 / CaCuSi4O 10 powder; MgCuSi4O 10 / CaCuSi4O 10 The powder was exfoliated by ultrasound to obtain the lamellar photothermal nanomaterial MgCuSi4O 10 / CaCuSi4O 10 ; SrCuSi4O 10 and BaCuSi4O 10 Synthesized by solid phase method, including: The raw materials SrCO3 / BaCO3, SiO2 and CuCO3 powders are fully ground and sintered at high temperature and cooled to obtain SrCuSi4O 10 / BaCuSi4O 10 The powder was then subjected to ultrasonic exfoliation to obtain the lamellar photothermal nanomaterial SrCuSi4O 10 and BaCuSi4O 10 .
[0012] Preferably, the molar ratio of the raw materials Mg(NO3)2·6H2O / CaCl2·2H2O, Cu(NO3)2·2.5H2O and tetraethyl orthosilicate is (0.5-2):(0.5-2):(2-8); Further preferably, the molar ratio of the raw materials Mg(NO3)2·6H2O / CaCl2·2H2O, Cu(NO3)2·2.5H2O and tetraethyl orthosilicate is 1:1:4.
[0013] Preferably, the molar ratio of the raw materials SrCO3 / BaCO3, SiO2 and CuCO3 is (0.5-2):(2-8):(0.5-2).
[0014] Further preferably, the molar ratio of the raw materials SrCO3 / BaCO3, SiO2 and CuCO3 is 1:4:1.
[0015] Preferably, MgCuSi4O is prepared 10 and CaCuSi4O 10 The final pH of the solution was adjusted to 12 with NH4OH.
[0016] Preferably, MgCuSi4O is prepared by hydrothermal method. 10 When the hydrothermal reaction temperature is 120-180 °C, the reaction time is 12-24 hours; More preferably, the hydrothermal reaction temperature is 150° C. and the reaction time is 24 hours.
[0017] Preferably, CaCuSi4O is prepared by hydrothermal method. 10 The hydrothermal reaction temperature is 250~350 ℃, and the reaction time is 12~96 hours.
[0018] More preferably, the reaction time is 24 hours.
[0019] Preferably, the solid phase method is used to synthesize SrCuSi4O 10 When the high temperature sintering treatment temperature is 950~1100 ℃, the treatment time is 12~20 hours; More preferably, the treatment time is 16 hours.
[0020] Preferably, BaCuSi4O is synthesized by solid phase method. 10 The high temperature sintering treatment temperature is 960~1100 ℃ and the treatment time is 12~48 hours.
[0021] More preferably, the treatment time is 24 hours.
[0022] Preferably, MgCuSi4O 10 / CaCuSi4O 10 The powder was ultrasonically exfoliated in the dispersion to obtain MCSn / CCSn, i.e., the lamellar photothermal nanomaterial MgCuSi4O 10 / CaCuSi4O 10 ; More preferably, the dispersion liquid may be N-methylpyrrolidone (NMP), tannic acid, acetone or dimethylformamide (DMF).
[0023] SrCuSi4O 10 / BaCuSi4O 10 The powder was subjected to high-power ultrasonic shedding in deionized water for 6-12 hours under ice bath conditions, and then centrifuged at 4000-8000 rpm for 10-20 minutes to collect SCSn / BCSn, i.e., the lamellar photothermal nanomaterial SrCuSi4O 10 / BaCuSi4O 10 .
[0024] The present invention also discloses the use of the above-mentioned photothermal nanomaterials that activate immunity to resist bacteria and promote bone formation in the preparation of bone implant materials / bone tissue engineering scaffolds.
[0025] The present invention also prepares a new photothermal responsive degradable composite implant with both antibacterial and osteogenesis properties, and proposes a new antibacterial strategy, which utilizes the synergistic effect of local thermal stimulation and metal ions to mobilize the host immune system, thereby killing pathogenic bacteria under relatively low temperature conditions.
[0026] Specifically, the present invention also discloses a photothermal responsive composite scaffold that activates immunity against bacteria and promotes bone differentiation, which is prepared by co-blending a bone repair material and the above-mentioned photothermal nanomaterial that activates immunity against bacteria and promotes bone differentiation; the composite scaffold has a porous multi-layer structure and has the dual functions of immune activation against bacteria and promoting bone differentiation.
[0027] The present invention also discloses a method for preparing the above-mentioned photothermal response composite scaffold for antibacterial and bone promotion through immune activation, comprising: The bone repair material was combined with the aforementioned photothermal nanomaterial XCuSi4O 10 Grind thoroughly and evenly to obtain mixed powder; among them, the photothermal nanomaterial XCuSi4O 10 Accounting for 1%~20% of the mass of Ca3SiO5 powder; The mixed powder was used as slurry and a photothermal responsive composite scaffold was prepared by 3D printing.
[0028] Preferably, the bone repair material is selected from bioceramics.
[0029] Further preferably, the above-mentioned materials include, but are not limited to, hydroxyapatite, tricalcium phosphate, zirconium oxide, iodine silicate glass, apatite-wollastonite, calcium silicate, dicalcium silicate, calcium carbonate and calcium magnesium silicate.
[0030] Preferably, the bone repair material is Ca3SiO5 powder.
[0031] The present invention discloses the application of the above-mentioned photothermal response composite scaffold for antibacterial and osteogenesis through immune activation as a bone tissue engineering scaffold.
[0032] Preferably, the photothermal responsive composite scaffold can be sterilized at 45-47°C, and then can promote the regeneration of infected bone under mild thermal stimulation at 40-42°C. It can be seen that since the photothermal responsive composite scaffold has photothermal conversion performance and contains Cu ions, the photothermal effect and Cu ion synergy can meet the needs of clearing bacteria at the infected site. On the other hand, thermal stimulation and ion synergy can enhance the immune system to clear external bacteria. At the same time, 41°C thermal stimulation can also promote bone defect repair, achieving a "kill two birds with one stone" therapeutic effect.
[0033] Compared with the prior art, the present invention has the following beneficial effects: The present invention first synthesizes a type of photothermal nanomaterial XCuSi4O that activates immunity, resists bacteria and promotes bone formation. 10 This photothermal nanomaterial has a two-zone near-infrared light-driven responsiveness, which can convert external near-infrared light energy into thermal energy. At the same time, the copper ions gradually released by its degradation can synergize with photothermal energy to achieve the removal of bacteria in the infected area.
[0034] On this basis, the present invention also incorporates the synthesized photothermal nanomaterials into bone repair materials (such as tricalcium silicate Ca3SiO5, C3S), and uses 3D printing technology to prepare personalized composite scaffolds with antibacterial and osteogenic functions, achieving safe and effective antibacterial, and successfully solving the technical defects of the prior art, such as low antibacterial efficiency, excessively high stimulation temperature that damages normal tissues, and being unfavorable to bone regeneration. The experiment of the present invention takes the composite scaffold MCS / C3S as an example, which has very good performance, mainly reflected in: 1) High strength mechanical properties, the compressive strength and compressive Young's modulus can reach 37.06 MPa and 261.23 MPa respectively; 2) Good degradation performance. Experimental results show that during the degradation process, Mg, Si and Cu ions in the MCS / C3S composite scaffold can be slowly released, which has a very significant effect on the body's immune regulation, sustained antibacterial and osteogenesis; 3) Excellent photothermal conversion performance. The MCS / C3S composite scaffold can meet the requirements of high-power laser thermal stimulation antibacterial and low-power thermal osteogenesis in the later stage after being implanted in the bone defect in the early stage of bone infection; 4) Near-infrared laser cooperates with Cu ions to achieve antibacterial effect. Under the condition of near-infrared light stimulation, the antibacterial effect of the MCS / C3S composite scaffold is significantly improved; 5) Thermal stimulation synergistically with Cu ions improves neutrophil phagocytosis of bacteria. In the presence of Cu ions and mild heat (45°C), the ability of neutrophils to phagocytose bacteria significantly increases to about 80%, indicating that the synergistic effect of 45°C mild heat stimulation and Cu ions can further clear bacteria from the infection site in the early stages of bacterial infection. Experiments also explain that the reason why thermal stimulation and ions synergistically improve neutrophil phagocytosis is because it increases the formation of NETs. 6) Thermal stimulation improves the ability of macrophages to clear neutrophils that engulf bacteria. Thermal stimulation and ion synergy can further improve the clearance of neutrophils by macrophages after neutrophils have completed the clearance of bacteria, thereby further killing bacteria. 7) Near-infrared laser-assisted MCS / C3S promoted osteogenesis, indicating that immune enhancement through synergistic mobilization of laser and ions can effectively eliminate foreign bacteria in the body, and show excellent bone reconstruction and repair effects in subsequent bone treatment.
[0035] Therefore, the new antibacterial strategy proposed for the first time in the present invention, i.e., utilizing the synergistic effect of local thermal stimulation and metal ions to mobilize the host immune system, can kill pathogenic bacteria under relatively low temperature conditions. The present invention has verified through experiments on bone injury infection models that the composite scaffold prepared for the first time in the present invention can eliminate Gram-positive and Gram-negative pathogens at relatively low temperatures (45-47°C), and then promote the regeneration of infected bones under mild thermal stimulation (40-42°C), and thus can be widely promoted and applied in bone implants or bone implant materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 SEM, TEM, XRD and XPS characterization of MCS; Figure 2 MCS / C3S ceramic scaffolds prepared for 3D printing; Figure 3 are the compressive strength and Young’s modulus of the scaffold; Figure 4 The degradation and ion release of MCS / C3S composite scaffold; Figure 5 The photothermal heating curves of C3S scaffold and MCS / C3S scaffold under near-infrared light stimulation; Figure 6 The temperature rise curve of MCS / C3S stent treated by near-infrared laser at different powers; Figure 7 The plate clones and antibacterial rates of C3S scaffold and MCS / C3S scaffold through synergistic antibacterial effects of photothermal and ion effects; Figure 8To qualitatively and quantitatively demonstrate that the synergistic effects of heat stimulation and Cu ions enhance the phagocytosis of bacteria by neutrophils; Fig. 9 The 2-week anti-infection and 10-week osteogenesis effects after treatment of in situ bone infection; the left picture shows Staphylococcus aureus ( S. aureus ) The anti-infection status of different groups was shown in the figure 2 weeks after the bone defect was infected; the right figure shows the results of CT imaging and quantitative analysis of the bone infection model after 10 weeks of treatment. (The first + / - in the C3S++ / +- and MCS / C3S++ / +- groups indicates the presence / absence of light during the 2-week anti-infection stage, and the second + / - indicates the presence / absence of light during the post-infection treatment). DETAILED DESCRIPTION
[0037] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0038] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0039] The present invention is further described in detail below in conjunction with the accompanying drawings: 1. XCuSi4O 10 Nanomaterial preparation Bright colors were highly prized in the ancient world. Even today, we can still see the remains of pigments and dyes created by every major culture. Two of the most famous synthetic blue pigments—Egyptian blue (CaCuSi4O10) and Han blue (BaCuSi4O 10 ), have similar chemical composition and structure, and both belong to the copper tetrasilicate series. Their general structural formula is XCuSi4O 10(X = Ca, Sr, Ba, etc.). In addition to being used as a pigment, this type of material also has the property of absorbing near-infrared light. Different application examples are as follows: Example 1: MgCuSi4O 10 Preparation of (MCS) nanomaterials MgCuSi4O was synthesized by hydrothermal method. 10 Nanomaterials. The specific synthesis steps are as follows: The raw materials are respectively taken in a molar ratio of Mg(NO3)2·6H2O:Cu(NO3)2·2.5H2O:tetraethyl orthosilicate ((C2H5O)4Si, TEOS) = (0.5-2): (0.5-2): (2-8) (the molar ratio is preferably 1:1:4) and dissolved in deionized water, and the final pH value of the solution is adjusted to 12 with NH4OH. Then the obtained gel mixture sample is placed in a sealed high-temperature reactor, heated to 120-180 ° C (preferably 150 ° C) and reacted for 12-24 hours (preferably 24 hours). After the reaction time is completed, the reactor is cooled to room temperature, the solid product is washed with water, and collected by vacuum filtration to obtain MgCuSi4O 10 , i.e. MCS powder.
[0040] The nanosheets were prepared by ultrasonic stripping. The synthesized MCS powder was dispersed in NMP (N-methylpyrrolidone) and stripped using an ultrasonic crusher to collect the MCSn nanosheets.
[0041] Finally, the collected MCSn nanosheets were subjected to TEM, XPS, XRD and other test characterizations ( Figure 1 ). SEM and TEM show that MCS is mainly a lamellar material. XRD result analysis: The analysis results of the diffraction peaks show that the material is composed of multiple crystalline phases, and its diffraction peaks appear at 27 positions with 2θ values of 15.4°, 17.3°, 19.4°, 20°, 21.8°, 22.2°, 24.6°, 25.1°, 25.9°, etc. (as marked in the figure above). By comparing the XRD spectrum of the sample with the spectrum in the standard database (such as JCPDS, ICSD, etc.), the phases present in the sample are identified to include SiO2, MgCuSi2O4, CuSiO3, MgSiO3 and Mg2SiO4. The corresponding specific positions are marked in the figure, indicating that the composite nanomaterial is composed of the above five substances, and the substance shows similar diffraction peaks compared with the crystal phases of other copper tetrasilicates (PDF#12-0511). XPS shows that the main elements in MCS are Mg, Cu, and Si.
[0042] Example 2: SrCuSi4O 10 Preparation of (SCS) nanomaterials SC nanomaterials were synthesized by solid phase synthesis: silica (SiO2), strontium carbonate (SrCO3) and copper carbonate (CuCO3) powders were mixed in a molar ratio of (2-8): (0.5-2): (0.5-2) (preferably 4:1:1). The mixture was uniformly ground, placed in a crucible, and heated at 960-1100 °C for 16 hours. The sintered mixture was re-ground and heated again at the same heating temperature. The obtained SCS raw material powder was purified using 1 M hydrochloric acid solution and deionized water. SCS nanomaterials are usually prepared by exfoliating the SCS raw material powder in deionized water using high power (1000 W) ultrasound in an ice bath for 6-12 hours. The SCS nanomaterials were centrifuged between 4000-8000 rpm for 15 minutes and collected for further use.
[0043] Example 3: CaCuSi4O 10 Preparation of (CCS) Nanomaterials The CCS material was synthesized by a hydrothermal method. CaCl2·2H2O, Cu(NO3)2·2.5H2O and sodium silicate [Na2O(SiO2)x (H2O)x] or tetraethyl orthosilicate solution were mixed in a molar ratio of (0.5-2): (0.5-2): (2-8). The mixture was dissolved in deionized water (30 mL), stirred and mixed thoroughly, and the pH value was adjusted to 12 using 14 M NH4OH. The gel mixture was placed in a reactor and heated at 350 °C for 12-96 hours (preferably 24 hours). After the reaction was completed, the container was cooled to room temperature, the solid product was washed with water, and the CCS raw material was collected by vacuum filtration. The CCS raw material was prepared by ultrasonic exfoliation as in Example 1 to obtain CCS nanomaterials.
[0044] Note: The x in Na2O(SiO2)x (H2O)x represents the molar ratio of SiO2 / Na2O, which should generally be between 1.5-3.5. The reagent x used this time is between 3.1-3.4, and it is a directly purchased raw material. The manufacturer information is: Macklin, batch number: S822245-500 mL.
[0045] Example 4: BaCuSi4O 10 Preparation of (BCS) nanomaterials The BCS material was synthesized by solid phase method. BaCO3, SiO2 and CuO were weighed according to the ratio in Example 1. The mixture was transferred to a crucible after grinding for 5-10 minutes. The crucible was heated to 950-1100°C in a furnace for 24 hours, then slowly cooled to 500-700°C, and finally cooled to room temperature. The preparation process of BCS nanosheet material was the same as that in Example 2.
[0046] The antibacterial efficiency of the photothermal nanomaterials prepared in Examples 1 to 4 was tested under two-zone near-infrared light drive, and the results are shown in Table 1 below: Table 1. XCuSi4O 10 and its antibacterial efficiency driven by second-zone near-infrared light
[0047] It can be seen from Table 1 that MgCuSi4O 10 The antibacterial efficiency is the highest. MgCuSi4O 10 Taking MCS as an example, relevant composite scaffold preparation and performance experimental tests were carried out.
[0048] 2. Preparation of 3D printed porous scaffolds by blending MCS and C3S (MCS / C3S composite scaffolds) The photothermal nanomaterial MCS powder and C3S powder are ground to make the two powders completely and evenly mixed, wherein the proportion of MCS in C3S is from 1.0-20 wt%, preferably 4%. The prepared mixed powder is used to prepare MCS / C3S composite scaffolds by 3D printer ( Figure 2 ). After the composite scaffold was dried at room temperature, it was immersed in a deionized water solution to solidify the composite scaffold into a ceramic scaffold with high mechanical strength. As can be seen from the figure, the C3S scaffold has a white porous multilayer structure, and the angle between the strands is about 60°. The MCS / C3S composite scaffold has a light blue porous multilayer structure, and the angle between the strands is about 60°.
[0049] 3. Performance study of MCS / C3S composite stent 1) Mechanical properties of MCS / C3S composite scaffolds The mechanical properties of the composite scaffold were tested using an Instron 5944 testing machine with a 20 KN range. The compression speed was 0.2-1 mm / min. The test was terminated at the breaking point of the strain-stress curve. The compressive Young's modulus was calculated based on the slope of the compressive strain-stress curve in the linear region (10-20% strain). The results showed that the compressive strength and compressive Young's modulus of the C3S sample were 14.97 MPa and 131.26 MPa, respectively, and the compressive strength and compressive Young's modulus of the MCS / C3S composite scaffold were 37.06 MPa and 261.23 MPa, respectively (as shown in the left and right of Figure 3, respectively).
[0050] 2) Degradation performance and ion release characteristics of MCS / C3S composite scaffolds As a bone implant material, the significant advantage is that it is degradable. As the scaffold degrades, the defect is gradually replaced by new bone for bone healing. The MCS / C3S composite scaffold prepared by the present invention is immersed in PBS solution to simulate the bone microenvironment, and the weight of the scaffold at different time points is recorded by weighing method. According to the final results, it can be known that ( Figure 4 ), the C3S scaffold degraded by 5% after 28 days, while the degradation rate of the scaffold after doping with MCS reached 15%. Along with the degradation, the ions in the scaffold were slowly released, and the released Mg, Cu, and Si ions were 6 ppm, 3.6 ppm, and 88 ppm respectively in 28 days. These ions have a positive effect on the body's immune regulation, sustained antibacterial and osteogenesis.
[0051] 3) Photothermal conversion performance of MCS / C3S composite scaffold Since MCS nanomaterials have near-infrared second-zone photothermal effect, loading them into C3S scaffolds gives the scaffolds this property, and the tissue penetration depth is deeper than that of 808 nm lasers. In the experiment, the scaffolds were irradiated with near-infrared lasers (1064 nm) under wet conditions (500 μL PBS), and the temperature changes and thermal imaging images were recorded by infrared thermal imaging cameras. The MCS / C3S composite scaffolds showed excellent photothermal performance ( Figure 5 and Figure 6 (shown): 0.9 W / cm 2 Within 3 minutes of laser irradiation, the stent can quickly heat up to above 45 °C. When the power is 0.6 W / cm 2 When the temperature of the scaffold can quickly rise to above 40°C and tend to be stable, the stimulation at this temperature has a promoting effect on the regulation of osteogenesis. Therefore, based on the above parameters, the scaffold can meet the requirements of high-power laser thermal stimulation antibacterial and low-power thermal osteogenesis in the later stage after being implanted in the bone defect in the early stage of bone infection.
[0052] 4) Near-infrared laser synergizes with Cu ions to achieve antibacterial The present invention co-cultures the MCS / C3S composite scaffold with Gram-positive bacteria Staphylococcus aureus and Gram-negative bacteria Escherichia coli for 3 hours, and then stimulates it with near-infrared light for 5 minutes. The bacteria on the surface of the MCS / C3S composite scaffold are peeled off by ultrasound, and the plate count method is finally used to evaluate the antibacterial effect of the MCS / C3S composite scaffold. The antibacterial effect of the experimental group reaches more than 99% ( Figure 7 ).
[0053] 5) Thermal stimulation synergizes with Cu ions to enhance neutrophil phagocytosis of bacteria Mobilizing and activating the body's own immune system to participate in antibacterial efforts is a feasible approach. The immune system is the body's first line of defense against external pathogens and is activated immediately after recognizing bacterial invasion. The innate immune system mobilizes a series of white blood cells, including neutrophils, eosinophils, basophils, lymphocytes, and monocytes to fight bacterial infections. Neutrophils are the most abundant type of white blood cells and play a first-line defense role in early bacterial infections. Neutrophils clear bacteria mainly by engulfing, releasing extracellular traps, and being cleared by macrophages after engulfing bacteria. Fever is a highly preserved protective mechanism against pathogen invasion in mammals during evolution, mainly through the release of cytokines by immune cells and increasing body temperature. Studies have shown that moderate heat stimulation can enhance the recruitment of a variety of immune cells, such as neutrophils, T lymphocytes, and macrophages, and enhance their vitality, promote the expression of inflammatory factors, and enhance the body's defense against bacterial invasion.
[0054] The present invention activates the recruitment and phagocytic ability of neutrophils through the synergistic effect of heat stimulation and Cu ions, thereby activating the autoimmune response and improving the antibacterial performance. Neutrophils and pre-stained Staphylococcus aureus ( S. aureus ) were co-cultured for 5.5 hours, during which different groups were subjected to 45°C heat stimulation with a 1064 nm laser. Finally, the cells were fixed, stained, and observed under a fluorescence microscope. The results showed that in the presence of Cu ions and laser irradiation, the ability of neutrophils to phagocytize bacteria was significantly increased to about 80% ( Figure 8 ). This indicates that the synergistic effect of 45 ℃ microthermal stimulation and Cu ions can further eliminate bacteria at the infection site in the early stage of bacterial infection.
[0055] 6) Near-infrared laser-assisted MCS / C3S to promote osteogenesis The in vivo treatment of bone infection of the present invention is simulated in a tibial defect model of 10-week-old male SD rats. Fig. 9 The results showed that the control group had severe cysts around the bone defect, while the bone infection in the experimental group had been completely cured, showing a normal tissue state. This shows that the immune enhancement mobilized by near-infrared laser and ion synergy can effectively eliminate foreign bacteria in the body, and in the subsequent 10-week bone treatment process, the experimental group showed excellent bone reconstruction and repair effects, while the control group had some obstacles to bone healing due to bacterial infection.
[0056] In summary, the existing technology aims to achieve the recruitment of immune cells by adjusting different components and synergizing with near-infrared light, as well as the balance between antibacterial conditions and subsequent osteogenic conditions. The near-infrared light combined with Cu ions used in the present invention synergistically improves the resistance of the immune system to foreign pathogens, rather than directly killing pathogens (bacteria), thereby balancing the realization of sterilization efficiency and tissue repair function. First, the effective sterilization temperature used in the present invention is lower than that of other inventions or documents, which can avoid burns to normal tissues due to excessively high temperatures during treatment; secondly, in addition to using physical and chemical means, the present invention first combines heat and autoimmune reactions and proposes that local thermal stimulation can mobilize immune cells to recruit to the site of infection, thereby utilizing the biological immune cells to improve antibacterial ability, minimizing the evolution and screening pressure on bacteria and avoiding the emergence of super bacteria.
[0057] Specifically, the present invention co-dopes degradable nanosheets with photothermal conversion with bone repair materials to prepare a scaffold with dual functions of implant material antibacterial and osteogenic differentiation. The principle is to enhance the removal of bacteria by autoimmune cells through photothermal and ion synergy, and use near-infrared light to drive local thermal stimulation and metal ions to activate the host immune system to sterilize antibacterial-osteoblastic implants, thereby preventing and resisting bacterial infection early after the placement of bone implant surgery, and subsequently promoting the repair of new bone regeneration after bone injury. In summary, the present invention simultaneously utilizes the synergistic methods of physics (near-infrared light), chemistry (ions) and biology (immune enhancement) to improve the antibacterial activity of bone repair materials and avoid the abuse of antibiotics leading to bacterial resistance. The MCS / C3S composite scaffold disclosed in the present invention can eliminate Gram-positive and Gram-negative pathogens at a relatively low temperature (45-47 ° C), and then promote the regeneration of infected bones under mild thermal stimulation (40-42 ° C).
[0058] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A type of photothermal nanomaterials that activate immunity to fight bacteria and promote bone growth, characterized in that: The molecular formula of the photothermal nanomaterial is XCuSi4O 10 , X is Mg, Sr, Ca or Ba, and the photothermal nanomaterial is a sheet material composed of multiple crystal phases.
2. The method for preparing a photothermal nanomaterial with antibacterial and bone-promoting properties through immune activation as claimed in claim 1, characterized in that: MgCuSi4O 10 and CaCuSi4O 10 Synthesized by hydrothermal method, including: The raw materials Mg(NO3)2·6H2O / CaCl2·2H2O, Cu(NO3)2·2.5H2O and tetraethyl orthosilicate were dissolved in water, and the pH value of the reaction system was adjusted to strong alkalinity to obtain a gel mixture; under closed conditions, the gel mixture was subjected to a hydrothermal reaction, cooled, washed and filtered to obtain MgCuSi4O 10 / CaCuSi4O 10 powder; MgCuSi4O 10 / CaCuSi4O 10 The powder was exfoliated by ultrasound to obtain the lamellar photothermal nanomaterial MgCuSi4O 10 / CaCuSi4O 10 ; SrCuSi4O 10 and BaCuSi4O 10 Synthesized by solid phase method, including: The raw materials SrCO3 / BaCO3, SiO2 and CuCO3 powders are fully ground and sintered at high temperature and cooled to obtain SrCuSi4O 10 / BaCuSi4O 10 The powder was then subjected to ultrasonic exfoliation to obtain the lamellar photothermal nanomaterial SrCuSi4O 10 and BaCuSi4O 10 .
3. The method for preparing a photothermal nanomaterial with antibacterial and bone-promoting properties through immune activation according to claim 2, characterized in that: The molar ratio of raw materials Mg(NO3)2·6H2O / CaCl2·2H2O, Cu(NO3)2·2.5H2O and tetraethyl orthosilicate is (0.5-2):(0.5-2):(2-8); The molar ratio of the raw materials SrCO3 / BaCO3, SiO2 and CuCO3 is (0.5-2):(2-8):(0.5-2).
4. The method for preparing a photothermal nanomaterial with antibacterial and bone-promoting properties through immune activation according to claim 2, characterized in that: Preparation of MgCuSi4O by hydrothermal method 10 The hydrothermal reaction temperature is 120-180℃ and the reaction time is 12-24 hours. 10 When the hydrothermal reaction temperature is 250-350℃, the reaction time is 12-96 hours; SrCuSi4O is synthesized by solid phase method 10 When the high temperature sintering temperature is 950~1100 ℃, the treatment time is 12~20 hours; BaCuSi4O 10 The high temperature sintering treatment temperature is 960~1100 ℃ and the treatment time is 12~48 hours.
5. The method for preparing a photothermal nanomaterial with antibacterial and bone-promoting properties through immune activation according to claim 2, characterized in that: MgCuSi4O 10 / CaCuSi4O 10 The powder was ultrasonically exfoliated in the dispersion to obtain MCSn / CCSn, i.e., the lamellar photothermal nanomaterial MgCuSi4O 10 / CaCuSi4O 10 ; SrCuSi4O 10 / BaCuSi4O 10 The powder was subjected to high-power ultrasonic shedding in deionized water for 6-12 hours under ice bath conditions, and then centrifuged at 4000-8000 rpm for 10-20 minutes to collect SCSn / BCSn, i.e., the lamellar photothermal nanomaterial SrCuSi4O 10 / BaCuSi4O 10 .
6. Use of the photothermal nanomaterials of claim 1 that are antibacterial and promote bone formation through immune activation in the preparation of bone implant materials / bone tissue engineering scaffolds.
7. A photothermal responsive composite scaffold for antibacterial and osteogenesis through immune activation, characterized in that: The composite scaffold is prepared by co-doping a bone repair material and a photothermal nanomaterial described in claim 1 that activates immunity to fight bacteria and promote bone differentiation. The composite scaffold has a porous multi-layer structure and has the dual functions of activating immunity to fight bacteria and promoting bone differentiation.
8. The method for preparing the photothermal responsive composite scaffold for antibacterial and bone promotion through immune activation according to claim 7, characterized in that: include: The bone repair material and the photothermal nanomaterial XCuSi4O 10 Grind thoroughly and evenly to obtain mixed powder; among them, the photothermal nanomaterial XCuSi4O 10 Accounting for 1%~20% of the mass of bone repair materials; The mixed powder was used as slurry and a photothermal responsive composite scaffold was prepared by 3D printing.
9. Use of the photothermal responsive composite scaffold for antibacterial and osteogenesis through immune activation as claimed in claim 7 as a bone tissue engineering scaffold.
10. The use according to claim 9, characterized in that The photothermal responsive composite scaffold can be sterilized at 45-47°C, and then can promote infected bone regeneration under mild thermal stimulation at 40-42°C.
Citation Information
Patent Citations
Method for preparing SrCuSi4O10 and BaCuSi4O10 blue pigments through hydrothermal technique
CN103601202A
Application of copper rankinite and compound biological material containing copper rankinite
CN111228484A
SrCuSi4O10-Ca3(PO4)2 composite biological ceramic, bone scaffold and application of bone scaffold
CN111848150A
Multifunctional composite porous scaffold as well as preparation method and application thereof
CN113633829A